2018
DOI: 10.1002/ppap.201800008
|View full text |Cite
|
Sign up to set email alerts
|

Nanosecond pulsed plasma discharge over a flowing water film: Characterization of hydrodynamics, electrical, and plasma properties and their effect on hydrogen peroxide generation

Abstract: A continuously flowing liquid film reactor driven by a variable nanosecond pulsed power supply, where plasma channels generated in argon propagate along the water film, was utilized to assess the effects of output voltage setting, pulse frequency, and gas/liquid flow rate on the generation of H 2 O 2 . Increasing the voltage significantly impacted the discharge current, resulting in hotter/denser plasma channels that increased the production rate of hydrogen peroxide but lowered the energy yield. Variation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 39 publications
1
37
0
Order By: Relevance
“…On [16,48,54]. However, considering the higher flow rate in the present work (10 mL/min) compared to other systems (1 mL/min for electrospray system and 4 mL/min for flowing water film), it could be concluded that AAGD treatment is comparable to analogs employing liquid flow for RONS production [16,54].…”
Section: Plasma-treatment Stabilizationmentioning
confidence: 50%
See 2 more Smart Citations
“…On [16,48,54]. However, considering the higher flow rate in the present work (10 mL/min) compared to other systems (1 mL/min for electrospray system and 4 mL/min for flowing water film), it could be concluded that AAGD treatment is comparable to analogs employing liquid flow for RONS production [16,54].…”
Section: Plasma-treatment Stabilizationmentioning
confidence: 50%
“…Despite the use of air as a process gas, low cost and simple setup, and the high concentration of RONS in treated liquid, power consumption of the present system (28 W) is higher compared to that of analogs, which could be a problem in large-scale application [16,40,48,54,57]. A problem with power consumption could be partially solved by the improvement of plasma-generator efficiency (currently only about 50% of power is absorbed in plasma) and fine-tuning the treatment parameters (matching liquid-flow rate and discharge power to achieve desired RONS concentration in the liquid without following dilution).…”
Section: Bactericidal Effect Of L -Phe Treated With Aagdmentioning
confidence: 99%
See 1 more Smart Citation
“…The work published here by M. Zhang et al demonstrates a miniaturization of the gas‐liquid water plasma reactor whereby the plasma is formed in a small gas cavity (3 mm deep) contacting a microchannel (500 μm wide) with flowing liquid water . In another case, Wandell et al utilize a small flowing water stream contacting a central gas core (4 mm gap with thin liquid film) with the electrical discharge propagating along the interface . The two different configurations of gas‐liquid plasma reactors allow for compact operation and characterization of the chemical and physical processes inside the reactor.…”
mentioning
confidence: 99%
“…The two different configurations of gas‐liquid plasma reactors allow for compact operation and characterization of the chemical and physical processes inside the reactor. Other papers in this issue include analysis of direct underwater discharges (Yang et al and Kozakova et al), study of pollutant treatment (Magureanu et al, Kozakova et al, Tampieri et al), determination of the fundamental species formation for plasma formed in contacting with a liquid water stream (X. Zhang et al, Tarabova et al, and Wandell et al), and analysis of plasma with organic liquids (Rezaei et al and Franclemont et al) . Of particular importance for chemical oxidation is the determination of hydroxyl radical, ·OH, concentrations and production using chemical probes (M. Zhang et al and X. Zhang et al), and in the case of an air plasma contacting the liquid the determination of nitrogen containing species and their interactions with species such as hydrogen peroxide (Tarabova et al) is necessary.…”
mentioning
confidence: 99%